A STUDY OF FLUID BED GRANULATION OF PRAVASTATIN TABLET USING DESIGN OF EXPERIMENTS - Kim, KANG MIN KIM; Pyo, Jae Sung (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to reduce size and weight of pravastatin tablet through quality by design approach; potential factors (spray rate, atomizing pressure, and inlet temperature) which could influence on the production process for critical process parameters of wet granulation using fluid-bed granulator were examined. Methods: The manufacturing process of the reduced weight and size formulation pravastatin tablet involves wet granulation, drying, granulate screening, blending, and tableting. Design of experiments study for wet granulation of the reduced weight/size pravastatin tablet was produced on 11 combinations of three factors (spray rate, atomizing pressure, and inlet temperature), which were chosen through initial risk assessment. The process of wet granulation was rated by measuring four responses: loss on drying (LOD) (%), bulk density (g/ml), product temperature (°C), and dissolution similarity (f2). Results: It was measured that LOD varied from 1.46 to 3.24%, bulk density from 0.34 to 0.51 g/ml, product temperature from 40.12 to 51.69°C, and dissolution (f2) of pravastatin from 52.14 to 58.91. Control strategy for wet granulation production of the reduced weight and size pravastatin tablet by our results demonstrated that the most optimized condition of three factors for wet granulation is spray rate (3–5 g/min), atomizing pressure (about 1 bar), and inlet temperature (65–90°C), respectively. Updated risk assessment and justification by all experimental data safely existed within the range of acceptance criteria were presented. Conclusion: It can be concluded that the ideal ranges of three factors (spray rate, atomizing pressure, and inlet temperature) in wet granulation were successfully identified.